Designing Tommy and Pokina Educative Language Game Software: a Transnational Popular Culture Project - Ekawati Marhaenny Dukut; Christine Ayu Wulandari; Thecla Brenda Chandrawati (SISFORMA, 2018)
Products of popular culture are many. One of those is educative language game software. Not only is a game useful in combating boredom, but a game can increase someone’s education capability. The PC (personal computer) a TOEFL-like game software created by the researchers applies the American TOEFL (Test of English as a Foreign Language) as a basis of the game.  It has transnational qualities because it integrates some local Indonesian culture into an American based English competence test. Being a transnational product, the game induces creativity for a number of Indonesian-English students to have a global imagination. The popular culture product named Tommy Pokina language game software is an educative game produced for 8th grade students studying at Junior High School. In designing the game, the method of symbolic analogy with the use of simple objects becomes the main characteristics of the game. In its visualization, the design process makes use of not only particular graphics, visualization effects, typography and interface; but also a number of other aspects. The aspects include the object’s illustrations, viewpoint, composition, and layout in developing the game’s visualization. These aspects are found to be valuable in designing the game.